Form of Consultation in the Era of Farooqi : عہد فاروقی میں مشاورت کی صورتیں - Saira Tariq; Ali Awais, Mian Muhammad (Al Khadim Research Journal of Islamic Culture and Civilization, 2020)
"Islam tells its followers to attain personal well-being through counseling system. Mutual cooperation and counseling is a natural requirement of the society. Historically counseling is characterized by both formal or professional and informal practices within both individual and group session. Counseling is an important part of an Islamic society. This Islamic rule of advisory was adopted in the early caliphate. The aim of this paper is to highlighted the advisory concepts in the era of Hazrat Umar Farooq (R.A)."